2018
DOI: 10.1111/cei.13218
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of YY1 reduce neutrophil infiltration by inhibiting IL-8 production via the PI3K-Akt-mTOR signaling pathway in rheumatoid arthritis

Abstract: Summary Our previous study revealed that Yin Yang 1(YY1) played an important part in promoting interleukin (IL)‐6 production in rheumatoid arthritis (RA). However, whether YY1 has any role in regulation of IL‐8 in RA remains unclear. YY1 and IL‐8 expression in RA patients were analyzed by real‐time polymerase chain reaction (PCR). Ingenuity pathway analysis (IPA) was used to analyze the signaling pathway involved in YY1‐induced IL‐8 production. The expression of YY1 and proteins involved in the pathway were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…IL-8 has been characterized to activate PI3K-Akt signaling through modulating phosphorylation/activation of Akt and S6 (MacManus et al 2007), while PI3K-Akt-mTOR signaling was also reported to enhance IL-8 production as feedback (Lin et al 2019), which comply with our findings in gastric cancer. On the contrary to IL-8, EMAP II is a pro-inflammatory cytokine that exerts anti-endothelial and anti-angiogenic activities through binding to VEGF receptors and disrupting fibronectin and VEGF signaling (Awasthi et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…IL-8 has been characterized to activate PI3K-Akt signaling through modulating phosphorylation/activation of Akt and S6 (MacManus et al 2007), while PI3K-Akt-mTOR signaling was also reported to enhance IL-8 production as feedback (Lin et al 2019), which comply with our findings in gastric cancer. On the contrary to IL-8, EMAP II is a pro-inflammatory cytokine that exerts anti-endothelial and anti-angiogenic activities through binding to VEGF receptors and disrupting fibronectin and VEGF signaling (Awasthi et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…IL-8 (also known as CXCL8) is a potent chemoattractant belonging to the CXC chemokine family [ 123 , 124 ]. In RA, IL-8 is probably responsible for recruiting cells into sites of inflammation [ 125 ], neutrophil activation, promoting their degranulation, and also release of superoxide and lysosomal enzymes, elevating cartilage damage and bringing pain [ 126 ].…”
Section: Ra Markers and Most Common Cytokines—potential Therapeutic Targetsmentioning
confidence: 99%
“…Dasatinib shares similar targets with imatinib and nilotinib, but dasatinib is more potent than imatinib and nilotinib at inhibiting tyrosine kinases (13). Dasatinib exhibits its own specific targets, such as PI3K and ERK (14), which are potent targets in RA treatment (15, 16). However, the effect of dasatinib on CIA is not known.…”
Section: Introductionmentioning
confidence: 99%